2019
DOI: 10.3892/etm.2019.7882
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PDIA3P regulates cell proliferation and invasion in non‑small cell lung cancer

Abstract: Increasing evidence has shown that long non-coding RNAs (lncRNAs) serve a critical role in tumor progression. The lncRNA protein disulfide isomerase family A member 3 pseudogene 1 (PDIA3P) is associated with the progression of oral squamous cell carcinoma and multiple myeloma. However, the roles of lncRNA PDIA3P in non-small cell lung cancer (NSCLC) remain unknown. In the present study, it was demonstrated that lncRNA PDIAP3 expression was significantly increased in patients with NSCLC, particularly in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Nevertheless, an increasing number of research have demonstrated that pseudogenes can control functional genes through various mechanisms, thus regulating diverse physiological and pathological processes, including carcinogenesis ( 16 , 51 ). Previous studies reported many tumor-related pseudogenes such as PTENP1 ( 53 , 54 ), DUXAP10 ( 55 ), SUMO1P3 ( 56 ), PDIA3P ( 57 ), PTTG3P ( 24 ), and DUXAP8 ( 58 ). In the present study, we first identified 632 differentially expressed pseudogenes in BC based on data from the dreamBase database.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, an increasing number of research have demonstrated that pseudogenes can control functional genes through various mechanisms, thus regulating diverse physiological and pathological processes, including carcinogenesis ( 16 , 51 ). Previous studies reported many tumor-related pseudogenes such as PTENP1 ( 53 , 54 ), DUXAP10 ( 55 ), SUMO1P3 ( 56 ), PDIA3P ( 57 ), PTTG3P ( 24 ), and DUXAP8 ( 58 ). In the present study, we first identified 632 differentially expressed pseudogenes in BC based on data from the dreamBase database.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Increasing reports indicate that lncRNA regulates the development and progression of human cancers. [11][12][13] LncRNAs may regulate proliferation, invasiveness and differentiation of tumor cells. 14 For example, HOXC-AS2 promotes metastasis of glioma cells by promoting ZEB1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…5  10 6 of pre-transfected MCF-7 cells and 2  10 6 of pre-transfected MDA-MB-231 cells were subcutaneously injected into the right back of nude mice (5 mice/group). Tumor volumes were calculated as the formula of 0.5  length  width2 at 6,9,12,15,18,21,24,27, and 30 days post-injection. Finally, these mice were sacrificed and the tumors were isolated and weighted.…”
Section: Animal Studiesmentioning
confidence: 99%
“… 8 , 9 , 10 , 11 Dysregulation of pseudogene-derived lncRNAs links to development of multiple diseases, including cancer. 11 For example, PDIA3P-derived lncRNA promotes proliferation and invasion of non-small cell lung cancer, 12 PCNAP1-derived lncRNA modulates hepatitis B virus replication and enhances tumor growth of liver cancer, 13 and KRT19P3-derived lncRNA inhibits proliferation and metastasis through COPS7A-mediated nuclear factor κB (NF-κB) pathway in gastric cancer. 14 Several studies conducted by our team and other labs have also suggested that pseudogenes and their RNA transcripts participate in carcinogenesis of breast cancer and serve as promising biomarkers for patients with breast cancer.…”
Section: Introductionmentioning
confidence: 99%